Corrigendum to “The overlooked effects of environmental impacts on root:shoot ratio in experiments and soil-crop models” [Sci. Total Environ. 955 (2024) 176738] - S.J. Seidel; S.H. Ahmadi; L. Weihermüller; A. Couëdel; G. Lopez; D. Behrend; B. Kamali; T. Gaiser; I.M. Hernández-Ochoa (Science of The Total Environment, 2026)

Microbial community adaptation in biosolid-based engineered soils - Diana P. Wehrendt; Leandro D. Guerrero; Anabella Tobler; Pedro R. Viera Farina; Patricia L. Fernandez; Paula Fontana; Melisa Altina; Rodrigo Pontiggia; Filipe Behrends Kraemer; Leonardo Erijman (Applied Soil Ecology, 2026)

Biosolids blended with edaphic supports mimic structural and biochemical features of natural soils and foster plant biomass growth - Filipe Behrends Kraemer; Diana P. Wehrendt; Anabella Tobler; Daiana Sainz; Lucas Barbieri Oliveri; Linda Jungwirth; Paula Fontana; Cristian Weigandt; Patricia L. Fernández; Melisa Altina; Leandro D. Guerrero; Rodrigo Pontiggia; et al. (European Journal of Soil Biology, 2025)

The overlooked effects of environmental impacts on root:shoot ratio in experiments and soil-crop models - S.J. Seidel; S.H. Ahmadi; L. Weihermüller; A. Couëdel; G. Lopez; D. Behrend; B. Kamali; T. Gaiser; I.M. Hernández-Ochoa (Science of The Total Environment, 2024)

Relatedness within colonies of three North American species of carpenter ants (Subgenus: Camponotus) and a comparison with relatedness estimates across Formicinae - B. A. Meadows; M. Emad; J. P. Hruska; J. Silva; G. J. Behrends; J. C. Girón; J. D. Manthey (Insectes Sociaux, 2023)

Spin vectors in the Koronis family: IV. Completing the sample of its largest members after 35 years of study - Stephen M. Slivan; Matthew Hosek; Max Kurzner; Alyssa Sokol; Sarah Maynard; Anna V. Payne; Arden Radford; Alessondra Springmann; Richard P. Binzel; Francis P. Wilkin; Emily A. Mailhot; Alan H. Midkiff; et al. (Icarus, 2023)

International VLBI Service for Geodesy and Astrometry - A. Nothnagel; T. Artz; D. Behrend; Z. Malkin (Journal of Geodesy, 2017)

Influence of the C rc regulator on the hierarchical use of carbon sources from a complete medium in P seudomonas - Ruggero La Rosa; Volker Behrends; Huw D. Williams; Jacob G. Bundy; Fernando Rojo (Environmental Microbiology, 2016)
Summary The C rc protein, together with the H fq protein, participates in catabolite repression in pseudomonads, helping to coordinate metabolism. Little is known about how C rc affects the hierarchy of metabolite assimilation from complex mixtures. Using proton Nuclear Magnetic Resonance ( NMR ) spectroscopy, we carried out comprehensive metabolite profiling of culture supernatants (metabolic footprinting) over the course of growth of both P seudomonas putida and P . aeruginosa , and compared the wild‐type strains with deletion mutants for crc . A complex metabolite consumption hierarchy was observed, which was broadly similar between the two species, although with some important differences, for example in sugar utilization. The order of metabolite utilization changed upon inactivation of the crc gene, but even in the C rc‐null strains some compounds were completely consumed before late metabolites were taken up. This suggests the presence of additional regulatory elements that determine the time and order of consumption of compounds. Unexpectedly, the loss of C rc led both species to excrete acetate and pyruvate as a result of unbalanced growth during exponential phase, compounds that were later consumed in stationary phase. This loss of carbon during growth helps to explain the contribution of the C rc/ H fq regulatory system to evolutionary fitness of pseudomonads.

Dense macrophytes influence the horizontal distribution of fish in floodplain lakes - Taise M. Lopes; Eduardo R. Cunha; João Carlos B. Silva; Rômulo D. L. Behrend; Luiz C. Gomes (Environmental Biology of Fishes, 2015)

Metabolic adaptations of Pseudomonas aeruginosa during cystic fibrosis chronic lung infections - V. Behrends; B. Ryall; J. E. A. Zlosnik; D. P. Speert; J. G. Bundy; H. D. Williams (Environmental Microbiology, 2013)
Summary Pseudomonas aeruginosa forms chronic infections in the lungs of cystic fibrosis (CF) patients, and is the leading cause of morbidity and mortality in patients with CF. Understanding how this opportunistic pathogen adapts to the CF lung during chronic infections is important to increase the efficacy of treatment and is likely to increase insight into other long‐term infections. Previous studies of P. aeruginosa adaptation and divergence in CF infections have focused on the genetic level, both identifying characteristic mutations and patterns of gene expression. However, these approaches are not sufficient to fully understand the metabolic changes that occur during long‐term infection, as metabolic regulation is complex and takes place on different biological levels. We used untargeted metabolic profiling (metabolomics) of cell supernatants (exometabolome analysis, or metabolic footprinting) to compare 179 strains, collected over time periods ranging from 4 to 24 years for the individual patients, representing a series of mostly clonal lineages from 18 individual patients. There was clear evidence of metabolic adaptation to the CF lung environment: acetate production was highly significantly negatively associated with length of infection. For amino acids, which are available to the bacterium in the lung environment, the tendency of isolates to evolve more efficient uptake was related to the biosynthetic cost of producing each metabolite; conversely, for the non‐mammalian metabolite trehalose, isolates had significantly reduced tendency to utilize this compound with length of infection. However, as well as adaptation across patients, there was also a striking degree of metabolic variation between the different clonal lineages: in fact, the patient the strains were isolated from was a greater source of variance than length of infection for all metabolites observed. Our data highlight the potential for metabolomic investigation of complex phenotypic adaptations during infection.

Repetitive activation of postsynaptic GABAA receptors by rapid, focal agonist application onto intact rat striatal neurones in vitro - Jan C. Behrends; John D. Lambert; Kimmo Jensen (Pflügers Archiv - European Journal of Physiology, 2002)